The Role of the Three Datuks in the Islamization of the Gowa Kingdom from the 16th Century to the 17th Century AD - Andi Wandi Hairuddin (Pustaka Digital Indonesia, 2025)
This research aims to determine the role of the Three Datuks in Islamization in the Kingdom of Gowa. This research is qualitative research that focuses on library research using four approaches, namely: the historical approach, the sociology of religion approach, the anthropology approach and the political approach. The data sources used in this research come from books, journals and articles related to research. Meanwhile, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation and drawing conclusions. The results of the research show that the role played by the Three Datuks in spreading Islam in the Kingdom of Gowa was to carry out a strategy. So even though the Tiga Datuk first arrived in the Gowa Kingdom, the first attempt at Islamization was made against the king and the palace of the Luwu Kingdom. This was because Tiga Datuk, in carrying out his missionary mission, first asked Malay migrants who had lived in Somba Opu for a long time to design an Islamization strategy. After King Luwu converted to Islam, the next strategy was to divide the missionary tasks according to the expertise of the Three Datuks. Datuk Patimang, an expert on Tauhid, served and lived in the Luwu Kingdom, while Datuk ri Bandang, who was known as a fiqh expert, was tasked with dealing with the people of Gowa and Tallo, then Datuk ri Tiro served in the Tiro area, Bulukumba, with more emphasis on the teachings of Sufism according to the conditions of the society he faced. The next strategy is to incorporate sara' (Islamic Sharia) into the cultural form of the Bugis-Makassar people, namely Pangngadakang/Pangngadereng and the final strategy is to carry out an Islamic war (Musu' Selleng) to spread Islam on the South Sulawesi Peninsula.